Internalization of Islamic Education Values Towards Local Wisdom (Pasaji Ponan Tradition) in Sumbawa Regency - Wahyuddin; Parhun, Muhammad (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This study discusses the Internalization of Islamic Education Values in the Pasaji Ponan Tradition of Sumbawa Regency. The aim is to find out how the internalization of Islamic education values in the pasaji ponan tradition is in the Sumbawa Regency community, how the impact of internalization of Islamic education values in the pasaji ponan tradition in the Sumbawa Regency community, how the relationship between Islamic education values and the pasaji ponan tradition. The type of research approach used in this study is a descriptive qualitative approach that aims to analyze the relationship between research variables and test hypotheses so as to describe a certain phenomenon. This research was conducted using observation, interview and documentation methods to reveal the process of internalization of these values. The results of this study indicate that the pasaji ponan tradition is an annual tradition that integrates Islamic values through the stages of transformation, transaction and transinternalization. This process involves the delivery of information, teaching and behavioral examples by traditional and village leaders and strengthening the mental attitude of the community. The impact of this tradition includes strengthening silaturrahmi, integration of educational values, prevention of social conflict and maintenance of relations between regions. In addition, this tradition also reflects the close relationship between Islamic, social and environmental values, where prayer and dhikr play an important role in strengthening relations with Allah and others.